Rotor Vibration Caused by Oil Whip and Treatment Method - Yufeng Li; Linjie Yang; Luji Wu; Zhigang Cao; Jingyuan Wang (Jixie chuandong)
The basic concepts and main characteristics of the oil whirl and oil whip are introduced， and the oil whip may cause serious damage to the unit， which must be paid great attention to and dealt with in time. Through the analysis of the frequency spectrogram， the orbit and the operating parameters of the fault unit， the relationship between them is pointed out. At last， the common measures to deal with the problem of oil whip are summarized， which provides a reference to deal with these problems.